Analysis of Aggregate Gradation to Improve The Characteristics of Geopolymer Based Asphalt Concrete - Akhmad Taufik Aditama; Januarti Jaya Ekaputri; Ervina Ahyudanari (IPTEK The Journal for Technology and Science, 2018)
The previous study showed that asphalt concrete using filler geopolymer generate a higher value of stability. On the other hand, the value of flow and the porosity of the asphalt concrete were out of the specification range. This study examines the aggregate gradation analysis to improve the characteristics of mixed asphalt concrete geopolymer. The gradation of aggregate is variated into three following the available specification. The range of specification is then separated into three, those are aggregate gradation upper specifications, middle specification, and lower specification. Filler comes from geopolymer paste, composed of fly ash which is mixed with an activator. Activator is an 8 molar concentration of NaOH solution and Na₂SiO₃. The weight ratio of Na₂SiO₃ over the weight of NaOH solution was 1.5. Geopolymer paste waited until reached the age of 28 days, then pounded up to meet the requirement size of the sieve No. 200. The test of mixture characteristics was conducted to see the comparison of performance from different gradations. The test results showed that middle gradation generating characteristics of the mixture which is higher than upper gradation and lower gradation.